Part-time employment as experiential learning: Soft skill development in English major undergraduates in Vietnam - Nguyễn Thị Kim, Phượng; Nguyễn, Thị Phương Thảo; Nguyễn, Thái An Phong (Tay Nguyen Journal of Sciences, 2025)
This study examines the role of part-time employment as a form of experiential learning that fosters soft skill development among undergraduate students majoring in foreign languages at Tay Nguyen University, Vietnam. Adopting a mixed-methods approach grounded in educational science theories -namely student involvement (Astin, 1984), identity development (Chickering & Reisser, 1993), and experiential learning (Kolb, 1984) - the research combines survey data (n = 247) with semi-structured interviews to explore students’ perceptions and experiences. Findings indicate that part-time work positively contributes to the development of key soft skills, including communication, time management, problem-solving, and teamwork. However, risks such as job mismatches, excessive workloads, and lack of guidance present notable challenges. Statistical analyses reveal a positive correlation between moderate work intensity and skill enhancement, whereas excessive work (>30 hours/week) is negatively associated with academic performance. The study underscores the potential of part-time employment to serve as a meaningful educational context when integrated into a supportive institutional framework. It concludes with targeted recommendations for students, universities, employers, and families to maximize the developmental value of student part-time work and align it with the goals of holistic education. Additional analysis highlights specific risks such as job mismatches, lack of institutional guidance, and exploitative practices (e.g., late payment).